Instagram: From Media Sharing Network To Learning Resource (Studi Terhadap Dua Akun Instagram) - Sakina Rahmania; Bagus Takwin (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
Social media or social networking sites can easily enable people to communicate in synchronous or asynchronous way and then collaboratively built a knowledge-based system and form a virtual learning community. This study aimed to investigate the application of a social media, especially Instagram as an informal learning resource by reviewing the relationship between Instagram features utilization and the learning engagement of the followers. This research was conducted by giving questionnaire to each of the two Instagram account to be examined. Based on the result of the measurement of learning engagement, using the engaging learning environment measurement tools, it was found that there was a strong and significant relationship between them with a relationship strength of 27.4%. Interaction is the indicator that has the strongest relationship with learning engagement, and Instagram live feature has the strongest positive relationship among other Instagram features. Thus, Instagram could be said as an engaging learning environment.